Injectable MMP-Responsive Nanotube-Modified Gelatin Hydrogel for Dental Infection Ablation - Ribeiro, Juliana S.; Bordini, Ester A. F. [UNESP]; Ferreira, Jessica A.; Mei, Ling; Dubey, Nileshkumar; Fenno, J. Christopher; Piva, Evandro; Lund, Rafael G.; Schwendeman, Anna; Bottino, Marco C. (Amer Chemical Soc, 2020)
A photocrosslinkable gelatin methacryloyl (GelMA) hydrogel has been widely examined in regenerative engineering because of its good cell-tissue affinity and degradability in the presence of matrix metalloproteinases. A halloysite aluminosilicate nanotube (HNT) is a known reservoir for the loading and sustained delivery of therapeutics. Here, we formulate injectable chlorhexidine (CHX)-loaded nanotube-modified GelMA hydrogel that is cytocompatible and biodegradable and provides sustained release of CHX for infection ablation while displaying good biocompatibility. The effects of HNTs and CHX on hydrogel degradability and mechanical properties, as well as on the kinetics of CHX release, and on the antimicrobial efficacy against oral pathogens were systematically assessed. Cytocompatibility in stem cells from human exfoliated deciduous teeth and inflammatory response in vivo using a subcutaneous rat model were determined. Our hydrogel system, that is, (CHX)-loaded nanotube-modified GelMA showed minimum localized inflammatory responses, supporting its ability for drug delivery applications. Moreover, we showed that the incorporation of CHX-loaded nanotubes reduces the mechanical properties, increases the swelling ratio, and diminishes the degradation rate of the hydrogels. Importantly, the presence of CHX-loaded nanotubes inhibits bacterial growth with minimal cell toxicity. Our findings provide a new strategy to modify GelMA hydrogel with chlorhexidine-loaded nanotubes for clinical use as an injectable drug delivery strategy for dental infection ablation.
Keywords: drug delivery; hydrogel; infection; endodontics; dentistry; matrix metalloproteinases